Clinical efficacy of nab-paclitaxel in patients with metastatic pancreatic cancer - De Luca R; Blasi L; Alù M; Gristina V; Cicero G (Dove Medical Press, 2018)
Rossella De Luca,1 Livio Blasi,2 Massimiliano Alù,2 Valerio Gristina,1 Giuseppe Cicero1 1Department of Surgical, Oncological and Oral Sciences, Section of Medical Oncology, University of Palermo, Palermo, Italy; 2Medical Oncology Unit, ARNAS Hospital Civico, Di Cristina, Benfratelli, Palermo, Italy Purpose: Pancreatic carcinoma is the neoplasia with the major mortality, and main standard treatments in this cancer increase survival but do not lead to complete recovery of the patient. The aim of this study was to evaluate the efficacy of Abraxane® (nab-paclitaxel) in Italian patients with metastatic pancreatic cancer (MPC).Patients and methods: We conducted a retrospective analysis of 80 patients. Overall survival (OS) was the primary end point for evaluating the efficacy of nab-paclitaxel in combination with gemcitabine treatment, while carbohydrate antigen 19-9 (CA 19-9) reduction, safety, progression-free survival (PFS), overall response rate and reduction in pain were secondary end points.Results: The median OS was 8 months, and the median PFS was 5 months. A considerable difference in CA 19-9 before and after treatment was observed. Descriptive and correlation analyses were done to examine the relationship between CA 19-9 response and OS. Linear regression analysis between OS and CA 19-9 response revealed that CA 19-9 is an important predictor of OS, showing a positive correlation.Conclusion: Nab-paclitaxel is a well-tolerated and effective treatment for patients affected by MPC. The drug showed an improved tolerability profile, significant pain relief and an increase in survival rate. Keywords: Abraxane, chemotherapy, pancreatic carcinoma, metastasis, CA 19-9, pain, overall survival